Degradable fracturing fluid composite thickening agent and preparation method thereof
By combining modified montmorillonite and polymer, a degradable fracturing liquid composite thickening agent was prepared, which solved the problem of poor effects of fracturing liquid in salt resistance and high temperature resistance, and achieved stable and efficient sand carrying effect and environmentally friendly degradation characteristics.
Patent Information
- Application Number
- CN202510326448.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-19
AI Technical Summary
At this stage, fracturing fluid has poor effect in salt resistance and high temperature resistance, and traditional thickeners have high temperature degradation and residue problems, which affects the environment and application breadth.
Sodium-based montmorillonite is used as raw material, and organic intercalation is modified by cetyl trimethylammonium bromide treatment. Combined with polymers such as acrylamide, acrylic acid and modified additives, a polyacrylamide structure is formed on the surface of the modified montmorillonite through polymerization, and a degradable fracturing liquid composite thickening agent is prepared.
The thickener exhibits stable chemical structure and good rheological properties at high temperatures, has good sand carrying capacity and salt resistance, reduces the dissolution of the salt layer and the damage to the formation, and its degradability reduces the pollution to the environment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fracturing fluid thickener preparation, and in particular to a degradable fracturing fluid composite thickener and a preparation method thereof. Background Art
[0002] Fracturing fluid is mainly a liquid used to ensure the intensity of the operation during oil and gas extraction. This liquid can transmit ground pressure, form cracks in the formation, carry proppants, and spread the proppants in the cracks, and reduce the loss of foreign liquid in the formation. Natural water-based fracturing fluid has a low viscosity. During use, in order to increase the application market of water-based fracturing fluid, enhance the viscosity of the water-based fracturing fluid system, and reduce the filtration performance of the fracturing fluid to make it have a better sand-carrying effect, the modification of thickeners has become the main research direction of domestic and foreign scholars. Traditional thickeners include natural plant gum derivatives, cellulose derivatives, and synthetic polymers. The use of a single thickener will cause high-temperature degradation, residues, and sensitivity to salt, which makes some fracturing fluids cannot be widely used or cause harm to the environment. Therefore, there is an urgent need for a thickener with a good thickening effect, which is resistant to high temperatures, salt, and not easy to produce residues. Summary of the invention
[0003] The purpose of the present invention is to provide a degradable composite thickener for fracturing fluid and a preparation method thereof, so as to solve the problem that the existing fracturing fluid has poor salt resistance and high temperature resistance.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a degradable composite thickener for fracturing fluid comprises the following steps: Step A1: Mix sodium montmorillonite and deionized water evenly, stir for 30-40 minutes at a speed of 800-1000 r / min and a temperature of 80-85° C., add hexadecyltrimethylammonium bromide, continue stirring for 2-3 hours, filter to remove the filtrate and dry to obtain modified montmorillonite; Step A2: uniformly mix acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide, a modified additive, modified montmorillonite and deionized water, introduce nitrogen to exhaust the air, stir and add an initiator at a speed of 120-150 r / min, a temperature of 60-70° C., and a pH value of 7, react for 5-7 hours, and dry to obtain a degradable fracturing fluid composite thickener.
[0005] Furthermore, the dosage ratio of sodium montmorillonite, deionized water and hexadecyltrimethylammonium bromide described in step A1 is 10g:200mL:6.5g.
[0006] Further, the mass ratio of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive described in step A2 is 74:16:8:2:5, the amount of modified montmorillonite is 1% of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, the amount of initiator is 1‰ of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, and the initiator is prepared by mixing ammonium persulfate and sodium bisulfite in a mass ratio of 2:1.
[0007] Further, the modified additive is prepared by the following steps: Step B1: β-cyclodextrin and pyridine are mixed, stirred and 4-toluenesulfonyl chloride is added at a speed of 200-300 r / min, a temperature of 0-5°C, and a pH value of 13-14, and the mixture is reacted for 25-30 hours to obtain pretreated cyclodextrin; the pretreated cyclodextrin is mixed with aqueous ammonia, and the mixture is reacted for 15-20 hours at a speed of 300-500 r / min and a temperature of 50-60°C to obtain amino cyclodextrin; Step B2: polyvinyl alcohol, boron trifluoride etherate and deionized water are mixed uniformly, and under the conditions of a rotation speed of 200-300r / min and a temperature of 60-65°C, epichlorohydrin is added under stirring and reflux, and the reaction is carried out for 2-3h, and then a hydroxide solution is added, and the temperature is raised to 75-80°C, and the reaction is continued for 3-5h to obtain functionalized polyvinyl alcohol, and amino cyclodextrin, functionalized polyvinyl alcohol and deionized water are mixed, and under the conditions of a rotation speed of 150-200r / min, a temperature of 60-70°C and a pH value of 11-12, the reaction is carried out for 4-6h to obtain a precursor; Step B3: Mix the precursor, lauric acid, dicyclohexylcarbodiimide and deionized water evenly, and react for 2-3 hours at a rotation speed of 150-200 r / min and a temperature of 95-100°C to obtain a modified precursor; mix the modified precursor, acrylic acid, p-toluenesulfonic acid and deionized water evenly, and react for 6-8 hours at a rotation speed of 150-200 r / min and a temperature of 95-100°C to obtain a modified additive.
[0008] Furthermore, the dosage ratio of β-cyclodextrin, pyridine and 4-toluenesulfonyl chloride in step B1 is 10mmol:60mL:73mmol, the dosage ratio of pretreated cyclodextrin and ammonia water is 1g:25mL, and the mass fraction of ammonia water is 25%.
[0009] Furthermore, the dosage ratio of polyvinyl alcohol, boron trifluoride ether, deionized water, oxychloropropane and hydroxide solution in step B2 is 40g:0.45g:200mL:0.1mol:10mL, the model of polyvinyl alcohol is 0388, the degree of polymerization is 300, the molecular weight is 10600, and the mass ratio of amino cyclodextrin and functionalized polyvinyl alcohol is 3:5.
[0010] Furthermore, the molar ratio of the amino group, lauric acid and dicyclohexylcarbodiimide on the precursor in step B3 is 1:1:1.2, the mass ratio of the modified precursor and acrylic acid is 8:13, and the amount of p-toluenesulfonic acid is 2% of the mass of acrylic acid.
[0011] Beneficial effects of the present invention: The present invention discloses a biodegradable fracturing fluid composite thickener, which uses sodium montmorillonite as a raw material, is treated with hexadecyltrimethylammonium bromide, and is subjected to organic intercalation modification to obtain modified montmorillonite; acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide, a modified additive, modified montmorillonite and deionized water are mixed, polymerized under the action of an initiator, and a polyacrylamide structure is formed on the surface of the modified montmorillonite to obtain a biodegradable fracturing fluid composite thickener.
[0012] The modified additive is prepared by treating β-cyclodextrin as a raw material with 4-toluenesulfonyl chloride so that the C6 hydroxyl group on the β-cyclodextrin reacts with the acyl chloride on the 4-toluenesulfonyl chloride to obtain a pretreated cyclodextrin, treating the pretreated cyclodextrin with ammonia water to undergo a nucleophilic substitution reaction to obtain an amino cyclodextrin, reacting polyvinyl alcohol with epichlorohydrin so that part of the hydroxyl groups on the polyvinyl alcohol reacts with the epoxy groups on the epichlorohydrin, and then closing the ring under the action of a sodium hydroxide solution to form a new epoxy group to obtain a functionalized polyvinyl alcohol, reacting the functionalized polyvinyl alcohol with the amino cyclodextrin so that the epoxy groups on the functionalized polyvinyl alcohol react with the amino groups on the amino cyclodextrin to obtain a precursor, reacting the precursor with lauric acid so that the amino groups in the precursor that have not been completely reacted react with the carboxyl groups on the lauric acid to obtain a modified precursor, and reacting the modified precursor with acrylic acid so that the hydroxyl groups on the modified precursor and the carboxyl groups on the acrylic acid are esterified to obtain a modified additive.
[0013] The modified additive contains cyclodextrin molecules. Compared with traditional guar gum, cyclodextrin has better high temperature resistance and good shear resistance, so that the thickener exhibits a stable chemical structure, good rheological properties and sand carrying capacity during high temperature use, thereby greatly reducing the dissolution of salt layers by the water fracturing fluid. At the same time, there is no residue after breaking the gel, which causes little damage to the formation and can effectively reduce damage to the reservoir. The polypropylene alcohol structure contained can increase the salt resistance of the thickener, making the thickener suitable for complex formation environments. At the same time, the organic part of the thickener can be degraded, thereby reducing the possibility of pollution to soil and water bodies. The addition of modified montmorillonite further enhances the sand carrying capacity of the thickener. DETAILED DESCRIPTION
[0014] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Embodiment 1, a method for preparing a degradable composite thickener for fracturing fluid, specifically comprising the following steps: Step A1: sodium montmorillonite and deionized water are mixed evenly, stirred for 30 minutes at a speed of 800 r / min and a temperature of 80° C., hexadecyltrimethylammonium bromide is added, stirring is continued for 2 hours, the filtrate is filtered to remove the filtrate and dried to obtain modified montmorillonite; Step A2: acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide, modified additives, modified montmorillonite and deionized water are mixed evenly, nitrogen is introduced to exhaust the air, and an initiator is added under the conditions of a rotation speed of 120 r / min, a temperature of 60° C. and a pH value of 7. The mixture is stirred and reacted for 5 hours, and dried to obtain a degradable fracturing fluid composite thickener.
[0016] The amount ratio of sodium montmorillonite, deionized water and hexadecyltrimethylammonium bromide described in step A1 is 10g:200mL:6.5g.
[0017] The mass ratio of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive described in step A2 is 74:16:8:2:5, the amount of modified montmorillonite is 1% of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, the amount of initiator is 1‰ of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, and the initiator is prepared by mixing ammonium persulfate and sodium bisulfite in a mass ratio of 2:1.
[0018] The modified additive is prepared by the following steps: Step B1: β-cyclodextrin and pyridine are mixed, stirred and 4-toluenesulfonyl chloride is added at a speed of 200 r / min, a temperature of 0°C, and a pH value of 13, and the mixture is reacted for 25 hours to obtain pretreated cyclodextrin; the pretreated cyclodextrin is mixed with aqueous ammonia, and the mixture is reacted for 15 hours at a speed of 300 r / min and a temperature of 50°C to obtain amino cyclodextrin; Step B2: polyvinyl alcohol, boron trifluoride ether and deionized water are mixed evenly, and under the conditions of a rotation speed of 300 r / min and a temperature of 65°C, epichlorohydrin is added under stirring and reflux, and the reaction is carried out for 3 hours, and then a hydroxide solution is added, and the temperature is raised to 80°C, and the reaction is continued for 5 hours to obtain functionalized polyvinyl alcohol, and amino cyclodextrin, functionalized polyvinyl alcohol and deionized water are mixed, and under the conditions of a rotation speed of 200 r / min, a temperature of 70°C and a pH value of 12, the reaction is carried out for 6 hours to obtain a precursor; Step B3: Mix the precursor, lauric acid, dicyclohexylcarbodiimide and deionized water evenly, and react at a speed of 200 r / min and a temperature of 100°C for 3 hours to obtain a modified precursor; mix the modified precursor, acrylic acid, p-toluenesulfonic acid and deionized water evenly, and react at a speed of 200 r / min and a temperature of 100°C for 8 hours to obtain a modified additive.
[0019] The dosage ratio of β-cyclodextrin, pyridine and 4-toluenesulfonyl chloride in step B1 is 10mmol:60mL:73mmol, the dosage ratio of pretreated cyclodextrin and ammonia water is 1g:25mL, and the mass fraction of ammonia water is 25%.
[0020] The dosage ratio of polyvinyl alcohol, boron trifluoride ether, deionized water, oxychloropropane and hydroxide solution described in step B2 is 40g:0.45g:200mL:0.1mol:10mL, the model of polyvinyl alcohol is 0388, the degree of polymerization is 300, the molecular weight is 10600, and the mass ratio of amino cyclodextrin and functionalized polyvinyl alcohol is 3:5.
[0021] The molar ratio of amino group, lauric acid and dicyclohexylcarbodiimide on the precursor in step B3 is 1:1:1.2, the mass ratio of the modified precursor and acrylic acid is 8:13, and the amount of p-toluenesulfonic acid is 2% of the mass of acrylic acid.
[0022] Embodiment 2, a method for preparing a degradable composite thickener for fracturing fluid, specifically comprising the following steps: Step A1: sodium montmorillonite and deionized water are mixed evenly, stirred for 35 minutes at a speed of 800 r / min and a temperature of 85° C., hexadecyltrimethylammonium bromide is added, stirring is continued for 2 hours, the filtrate is filtered to remove the filtrate and dried to obtain modified montmorillonite; Step A2: acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide, modified additives, modified montmorillonite and deionized water are mixed evenly, nitrogen is introduced to exhaust the air, and an initiator is added under the conditions of a rotation speed of 150 r / min, a temperature of 65° C. and a pH value of 7. The mixture is stirred and reacted for 6 hours, and dried to obtain a degradable fracturing fluid composite thickener.
[0023] The amount ratio of sodium montmorillonite, deionized water and hexadecyltrimethylammonium bromide described in step A1 is 10g:200mL:6.5g.
[0024] The mass ratio of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive described in step A2 is 74:16:8:2:5, the amount of modified montmorillonite is 1% of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, the amount of initiator is 1‰ of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, and the initiator is prepared by mixing ammonium persulfate and sodium bisulfite in a mass ratio of 2:1.
[0025] The modified additive is prepared by the following steps: Step B1: β-cyclodextrin and pyridine are mixed, stirred and 4-toluenesulfonyl chloride is added at a speed of 200 r / min, a temperature of 3°C, and a pH value of 13, and the mixture is reacted for 30 hours to obtain pretreated cyclodextrin; the pretreated cyclodextrin is mixed with aqueous ammonia, and the mixture is reacted for 18 hours at a speed of 300 r / min and a temperature of 55°C to obtain amino cyclodextrin; Step B2: polyvinyl alcohol, boron trifluoride etherate and deionized water are mixed uniformly, and under the conditions of a rotation speed of 300 r / min and a temperature of 60°C, epichlorohydrin is added under stirring and reflux, and the reaction is carried out for 3 hours, and then a hydroxide solution is added, and the temperature is raised to 75°C, and the reaction is continued for 4 hours to obtain functionalized polyvinyl alcohol, and amino cyclodextrin, functionalized polyvinyl alcohol and deionized water are mixed, and under the conditions of a rotation speed of 150 r / min, a temperature of 65°C and a pH value of 11, the reaction is carried out for 5 hours to obtain a precursor; Step B3: Mix the precursor, lauric acid, dicyclohexylcarbodiimide and deionized water evenly, and react at a speed of 150 r / min and a temperature of 100°C for 2 hours to obtain a modified precursor. Mix the modified precursor, acrylic acid, p-toluenesulfonic acid and deionized water evenly, and react at a speed of 200 r / min and a temperature of 95°C for 7 hours to obtain a modified additive.
[0026] The dosage ratio of β-cyclodextrin, pyridine and 4-toluenesulfonyl chloride in step B1 is 10mmol:60mL:73mmol, the dosage ratio of pretreated cyclodextrin and ammonia water is 1g:25mL, and the mass fraction of ammonia water is 25%.
[0027] The dosage ratio of polyvinyl alcohol, boron trifluoride ether, deionized water, oxychloropropane and hydroxide solution described in step B2 is 40g:0.45g:200mL:0.1mol:10mL, the model of polyvinyl alcohol is 0388, the degree of polymerization is 300, the molecular weight is 10600, and the mass ratio of amino cyclodextrin and functionalized polyvinyl alcohol is 3:5.
[0028] The molar ratio of amino group, lauric acid and dicyclohexylcarbodiimide on the precursor in step B3 is 1:1:1.2, the mass ratio of the modified precursor and acrylic acid is 8:13, and the amount of p-toluenesulfonic acid is 2% of the mass of acrylic acid.
[0029] Embodiment 3, a method for preparing a degradable composite thickener for fracturing fluid, specifically comprising the following steps: Step A1: sodium montmorillonite and deionized water are mixed evenly, stirred for 40 minutes at a speed of 1000 r / min and a temperature of 85° C., hexadecyltrimethylammonium bromide is added, stirring is continued for 3 hours, the filtrate is filtered to remove the filtrate and dried to obtain modified montmorillonite; Step A2: acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide, modified additives, modified montmorillonite and deionized water are mixed evenly, nitrogen is introduced to exhaust the air, and an initiator is added under the conditions of a rotation speed of 150 r / min, a temperature of 70° C. and a pH value of 7. The mixture is stirred and reacted for 7 hours, and dried to obtain a degradable fracturing fluid composite thickener.
[0030] The amount ratio of sodium montmorillonite, deionized water and hexadecyltrimethylammonium bromide described in step A1 is 10g:200mL:6.5g.
[0031] The mass ratio of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive described in step A2 is 74:16:8:2:5, the amount of modified montmorillonite is 1% of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, the amount of initiator is 1‰ of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive, and the initiator is prepared by mixing ammonium persulfate and sodium bisulfite in a mass ratio of 2:1.
[0032] The modified additive is prepared by the following steps: Step B1: β-cyclodextrin and pyridine are mixed, stirred and 4-toluenesulfonyl chloride is added at a speed of 300 r / min, a temperature of 5°C, and a pH value of 14, and the mixture is reacted for 30 hours to obtain pretreated cyclodextrin; the pretreated cyclodextrin is mixed with aqueous ammonia, and the mixture is reacted for 20 hours at a speed of 500 r / min and a temperature of 60°C to obtain amino cyclodextrin; Step B2: polyvinyl alcohol, boron trifluoride ether and deionized water are mixed evenly, and under the conditions of a rotation speed of 300 r / min and a temperature of 65°C, epichlorohydrin is added under stirring and reflux, and the reaction is carried out for 3 hours, and then a hydroxide solution is added, and the temperature is raised to 80°C, and the reaction is continued for 5 hours to obtain functionalized polyvinyl alcohol, and amino cyclodextrin, functionalized polyvinyl alcohol and deionized water are mixed, and under the conditions of a rotation speed of 200 r / min, a temperature of 70°C and a pH value of 12, the reaction is carried out for 6 hours to obtain a precursor; Step B3: Mix the precursor, lauric acid, dicyclohexylcarbodiimide and deionized water evenly, and react at a speed of 200 r / min and a temperature of 100°C for 3 hours to obtain a modified precursor; mix the modified precursor, acrylic acid, p-toluenesulfonic acid and deionized water evenly, and react at a speed of 200 r / min and a temperature of 100°C for 8 hours to obtain a modified additive.
[0033] The dosage ratio of β-cyclodextrin, pyridine and 4-toluenesulfonyl chloride in step B1 is 10mmol:60mL:73mmol, the dosage ratio of pretreated cyclodextrin and ammonia water is 1g:25mL, and the mass fraction of ammonia water is 25%.
[0034] The dosage ratio of polyvinyl alcohol, boron trifluoride ether, deionized water, oxychloropropane and hydroxide solution described in step B2 is 40g:0.45g:200mL:0.1mol:10mL, the model of polyvinyl alcohol is 0388, the degree of polymerization is 300, the molecular weight is 10600, and the mass ratio of amino cyclodextrin and functionalized polyvinyl alcohol is 3:5.
[0035] The molar ratio of amino group, lauric acid and dicyclohexylcarbodiimide on the precursor in step B3 is 1:1:1.2, the mass ratio of the modified precursor and acrylic acid is 8:13, and the amount of p-toluenesulfonic acid is 2% of the mass of acrylic acid.
[0036] Comparative Example 1: Compared with Example 1, montmorillonite is used instead of modified montmorillonite, and the other steps are the same.
[0037] Comparative Example 2: Compared with Example 1, ethylenediamine was used to replace the amino cyclodextrin in this comparative example, and the remaining steps were the same.
[0038] Comparative Example 3: Compared with Example 1, acetic acid is used instead of lauric acid, and the remaining steps are the same.
[0039] Comparative Example 4: Compared with Example 1, in this comparative example, amino cyclodextrin, acrylic acid, dicyclohexylcarbodiimide and deionized water are uniformly mixed, and the reaction is carried out at a speed of 200 r / min and a temperature of 30°C for 8 hours. The obtained product replaces the modified additive, and the remaining steps are the same.
[0040] The thickeners prepared in Examples 1-3 and Comparative Examples 1-4 were mixed in the following mass percentages: 0.6% thickener, 0.25% potassium chloride, 0.1% tetradecyltrimethylammonium bromide, 0.1% ammonium persulfate and 0.2% OP-10, with the remainder being water, and the pH value was adjusted to 7 to prepare a fracturing base fluid. The fracturing base fluid was stirred at a shear rate of 170 s -1 At a temperature of 20°C, a six-speed rotary viscometer was used to test the apparent viscosity. The temperature was raised to 120°C and the apparent viscosity was tested after shearing for 1.5 hours. Sodium chloride was added to the fracturing base fluid to form a solution with a sodium ion concentration of 30,000 mg / L. The apparent viscosity was tested. The test results are shown in Table 1 below.
[0041] Table 1
[0042] It can be seen from Table 1 that the present invention has good salt resistance and high temperature resistance effects.
[0043] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a degradable composite thickener for fracturing fluid, characterized in that: The specific steps include: Step A1: After mixing sodium montmorillonite and deionized water, cetyltrimethylammonium bromide is added, stirring is continued, the filtrate is filtered to remove the filtrate and dried to obtain modified montmorillonite; Step A2: uniformly mix acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide, a modified additive, modified montmorillonite and deionized water, introduce nitrogen to exhaust the air, stir and add an initiator, react, and dry to obtain a degradable fracturing fluid composite thickener.
2. The method for preparing a degradable composite thickener for fracturing fluid according to claim 1, characterized in that: The amount ratio of sodium montmorillonite, deionized water and hexadecyltrimethylammonium bromide described in step A1 is 10g:200mL:6.5g.
3. The method for preparing a degradable composite thickener for fracturing fluid according to claim 1, characterized in that: The mass ratio of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive described in step A2 is 74:16:8:2:5, and the amount of modified montmorillonite is 1% of the sum of the mass of acrylamide, acrylic acid, 2-methyl-2-acrylamidopropanesulfonic acid, N,N-dimethylacrylamide and the modifying additive.
4. The method for preparing a degradable composite thickener for fracturing fluid according to claim 1, characterized in that: The modified additive is prepared by the following steps: Step B1: β-cyclodextrin and pyridine are mixed and stirred, and 4-toluenesulfonyl chloride is added to react to obtain pretreated cyclodextrin, and the pretreated cyclodextrin is mixed and reacted with ammonia water to obtain amino cyclodextrin; Step B2: polyvinyl alcohol, boron trifluoride etherate and deionized water are mixed, stirred and refluxed, and epichlorohydrin is added to react, and then a hydroxide solution is added, and the temperature is raised to continue the reaction to obtain functionalized polyvinyl alcohol, and amino cyclodextrin, functionalized polyvinyl alcohol and deionized water are mixed and reacted to obtain a precursor; Step B3: The precursor, lauric acid, dicyclohexylcarbodiimide and deionized water are mixed and reacted to obtain a modified precursor, and the modified precursor, acrylic acid, p-toluenesulfonic acid and deionized water are mixed and reacted to obtain a modified additive.
5. The method for preparing a degradable composite thickener for fracturing fluid according to claim 4, characterized in that: The dosage ratio of β-cyclodextrin, pyridine and 4-toluenesulfonyl chloride in step B1 is 10mmol:60mL:73mmol, and the dosage ratio of pretreated cyclodextrin and ammonia water is 1g:25mL.
6. The method for preparing a degradable composite thickener for fracturing fluid according to claim 4, characterized in that: The amount ratio of polyvinyl alcohol, boron trifluoride ether, deionized water, oxychloropropane and hydroxide solution in step B2 is 40g:0.45g:200mL:0.1mol:10mL, and the mass ratio of amino cyclodextrin to functionalized polyvinyl alcohol is 3:
5.
7. The method for preparing a degradable composite thickener for fracturing fluid according to claim 4, characterized in that: The molar ratio of the amino group, lauric acid and dicyclohexylcarbodiimide on the precursor in step B3 is 1:1:1.2, and the mass ratio of the modified precursor and acrylic acid is 8:
13.
8. A degradable composite thickener for fracturing fluid, characterized by: Prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-temperature-resistant polymer thickening agent for oil field fracturing fluid as well as preparation method and application of thickening agent
CN104449643A
Oil-based drilling fluid
CN108329897A
Preparation method of environment-friendly water-saving fracturing fluid
CN111394086A
Modified nano-montmorillonite and preparation method thereof, polymer fracturing fluid synergist and preparation method and application of polymer fracturing fluid synergist
CN114395388A
Clean fracturing fluid thickening agent for oil well and preparation method thereof
CN116948107A
Cited By
Preparation method of thickening agent for fracturing
CN121609838A